Pengaruh Kompensasi dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Serasi Autoraya (TRAC) - Nurmala Agustina; Isyana Emita (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
Sinar Inti Telaga was founded in 1986, then transformed into PT Serasi Autoraya in 1990 by introducing the trademark "Toyota A Car". PT. Serasi Autoraya (TRAC) is an international subsidiary. Tbk which is now widely known as one of the largest transportation and logistics service companies in Indonesia. The aim of this research is to determine the effect of compensation and work discipline on the performance of PT. Serasi Autoraya (TRAC) in this research uses independent variables, namely compensation (X1) and work discipline (X2) as well as the dependent variable, namely employee performance (Y). The population of this study were employees of PT. Serasi Autoraya (TRAC). The sample used the Puprosive Sampling method, data collection by collecting questionnaires online with Google from to 50 respondents. The method in this research uses quantitative statistical methods. Quantitative statistical analysis includes validity tests, reliability tests, multiple linear analysis. Other hypothesis testing includes classical assumption tests, including data normality test, multicollinearity test, heteroscedasticity test, T test, F test, and coefficient of determination test (R2). The data was processed using the SPSS (Statistical Package for Social Science) 25.0 photo windows program. The test results of the T (Partial) test on the compensation variable (X1) show that the sig 0.004 < 0.05 and t value 3,028 > 2,010 (t table) test results on the T (Partial) test on the work discipline variable, namely 0.000 < 0.05 and t value 6,081 > 2,010 (t table). The test results of the F test (Simultaneous) show that the sig value is 0.000 < 0.05 and the calculated f value is 49,966 > 3.19 (f table) and it can be concluded that compensation (X1) and work discipline (X2) have a positive and significant effect on performance employee (Y).